Inovasi Tata Kelola Izin Mendirikan Bangunan di Kota Pontianak - Elfarda Sammaulana Ikhsani; M. S. Rifki (Research and Development Agency Ministry of Home Affairs, 2017)
This research is about Implementation of Building Permit Policy (IMB) in Dinas Cipta Karya Tata Ruang dan Perumahan (DCKTRP) of Pontianak City. The study aims to determine the implementation of Local Regulation (Perda) Pontianak City No 3 of 2008 on Building on the practice of making IMB and to know the innovations made DCKTRP. The research method used is descriptive with qualitative approach, while the data collection technique used in-depth interview and documentation. The results showed the implementation of Perda Pontianak City No 3 of 2008 on the Building has been done well. This is indicated by the service provided is quite optimal and the completion time permits can be completed in just one day. The cutting time is due to various innovations made by the Department such as IMB Bleaching and one day service. Even so, in the implementation of Perda still encountered several inhibiting factors of implementation due to several things such as lack of computer facilities, servers, service operators, and limited support facilities. DCKTRP as a leading sector IMB should continue to provide socialization on a regular basis, and complement the facilities needed to support the service IMB for the community. Furthermore, DCKTRP needs to review the Perda Pontianak No 3 of 2008, because the innovations that have been conducted do not currently have legal and informal.